A series of robust genetic indicators for definitive identification of cardiomyocytes. (August 2016) - Yan, Jianyun; Zhang, Lu; Sultana, Nishat; Oh, Jae Gyun; Wu, Bingruo; Hajjar, Roger J.; Zhou, Bin; Cai, Chen-Leng
Abstract: Definitively identifying the cell type of newly generated cells in the heart and defining their origins are central questions in cardiac regenerative medicine. Currently, it is challenging to ascertain the myocardial identity and to track myocardial progeny during heart development and disease due to lack of proper genetic tools. This may lead to many misinterpretations of the findings in cardiac regenerative biology. In this study, we developed a set of novel mouse models by inserting double reporter genes nlacZ/H2B-GFP, mGFP/H2B-mCherry into the start codon of Tnnt2 and Myh6 . nlacZ (nuclear lacZ) and mGFP (membrane GFP) are flanked by two LoxP sites in these animals. We found that the reporter genes faithfully recapitulated Tnnt2 and Myh6 cardiac expression from embryonic stage and adulthood. The reporter mice provide unprecedented robustness and fidelity for visualizing and tracing cardiomyocytes with nuclear or cell membrane localization signals. These animal models offer superior genetic tools to meet a critical need in studies of heart development, cardiac stem cell biology and cardiac regenerative medicine.